Analisis Kecerdasan Visual Spasial Ditinjau Dari Dominasi Otak Peserta Didik - Usmanto, Kharisma Adi Ratna; Muzdalipah, Ipah; Herawati, Linda (Imajiner: Jurnal Matematika dan Pendidikan Matematika, 2025)
This study aims to describe the visual-spatial intelligence of students in terms of right-brain and left-brain dominance. This study uses a qualitative descriptive method. The data collection techniques in this study include a brain dominance questionnaire, a visual-spatial intelligence test, and interviews. The subjects of this study consisted of four eighth-grade students from SMP Negeri 5 Kota Tasikmalaya. The selection of subjects was based on the consideration that the students exhibited consistent characteristics of right and left-brain dominance, met all criteria for visual-spatial intelligence regardless of correct or incorrect answers, and were able to provide clear and complete information. The results of the study indicate that subjects with right-brain dominance (S-2 and S-8) meet the characteristics of visual-spatial intelligence, namely imagination, conceptualization, problem-solving, and pattern recognition. Subjects S-2 and S-8 exhibit characteristics of right-brain dominance that are intuitive, imaginative, creative, and visual, with a tendency to use visuals in developing strategies. Then, subjects with left-brain dominance (S-13 and S-19) meet the characteristics of visual-spatial intelligence, namely visualization, conceptualization, problem solving, and pattern recognition. Subjects S-13 and S-19 exhibit characteristics of left-brain dominance that are logical, systematic, and concept-based, with a structured approach. These differences indicate that brain dominance influences how learners understand information, plan solution strategies, and evaluate results in visual-spatial tasks.